Atrial Tissue Pro‐Fibrotic M2 Macrophage Marker CD163+, Gene Expression of Procollagen and B‐Type Natriuretic Peptide. Issue 11 (2nd June 2020) - Watson, Chris J.; Glezeva, Nadezhda; Horgan, Stephen; Gallagher, Joe; Phelan, Dermot; McDonald, Ken; Tolan, Michael; Baugh, John; Collier, Patrick; Ledwidge, Mark
Abstract : Background: Atrial tissue fibrosis is linked to inflammatory cells, yet is incompletely understood. A growing body of literature associates peripheral blood levels of the antifibrotic hormone BNP (B‐type natriuretic peptide) with atrial fibrillation (AF). We investigated the relationship between pro‐fibrotic tissue M2 macrophage marker Cluster of Differentiation (CD)163+, atrial procollagen expression, and BNP gene expression in patients with and without AF. Methods and Results: In a cross‐sectional study design, right atrial tissue was procured from 37 consecutive, consenting, stable patients without heart failure or left ventricular systolic dysfunction, of whom 10 had AF and 27 were non‐AF controls. Samples were analyzed for BNP and fibro‐inflammatory gene expression, as well as fibrosis and CD163+. Primary analyses showed strong correlations (all P <0.008) between M2 macrophage CD163+ staining, procollagen gene expression, and myocardial BNP gene expression across the entire cohort. In secondary analyses without multiplicity adjustments, AF patients had greater left atrial volume index, more valve disease, higher serum BNP, and altered collagen turnover markers versus controls (all P <0.05). AF patients also showed higher atrial tissue M2 macrophage CD163+, collagen volume fraction, gene expression of procollagen 1 and 3, as well as reduced expression of the BNP clearance receptor NPRC (all P <0.05). Atrial procollagen 3 gene expression was correlated with fibrosis and BNP gene expression was correlated with serum BNP. Conclusions: Elevated atrial tissue pro‐fibrotic M2 macrophage CD163+ is associated with increased myocardial gene expression of procollagen and anti‐fibrotic BNP and is higher in patients with AF. More work on modulation of BNP signaling for treatment and prevention of AF may be warranted.